Differential Degradation of TRA2A and PYCR2 Mediated by Ubiquitin E3 Ligase E4B - Lu, Yao; Jiang, Bo; Peng, Kangli; Li, Shasha; Liu, Xiangnan; Wang, Bufan; Chen, Yuntian; Wang, Tiepeng; Zhao, Bo (Frontiers in Cell and Developmental Biology, 2022)
E4B belongs to U-box E3 ligase family and functions as either an E3 or an E4 enzyme in protein ubiquitination. Transformer2A (TRA2A) and Pyrroline-5-carboxylate reductase 2 (PYCR2) are related to the development of cancer and overexpressed in many cancer cells. The degradation of TRA2A and PYCR2 mediated by ubiquitin-proteasome system (UPS) has not been reported. In this study, we validated that E4B could ubiquitinate TRA2A and PYCR2 as an E3 ligase both in vitro and in HEK293 cells. E4B mediated the degradation by forming K11- and K48- linked polyubiquitin chains on TRA2A and PYCR2. E4B regulated alternative splicing function of TRA2A and affected RSRC2 transcription in HEK293 cells. Although E4B is overexpressed, however, it hardly degraded TRA2A and PYCR2 in hepatocellular carcinoma (HCC) cells, suggesting there are other mechanisms on the degradation of TRA2A and PYCR2 in HCC cells. We finally reported that E4B interacted with substrates via its variable region.